Integrating Islamic Educational Values through Sasak Muslim Death Rituals: An Ethnographic Study - Lalu Nasrulloh; Sumarsi Sumarsi; Ali Nurdin; Kusaeri Kusaeri (AL-ISHLAH: Jurnal Pendidikan, 2025)
Death rituals in local Muslim communities are not merely cultural expressions but also potential platforms for transmitting Islamic educational values. This study explores how death traditions among the Sasak Muslim community serve as a medium for informal Islamic education through the integration of cultural and religious elements. Using an ethnographic approach, data were collected through participatory observation, in-depth interviews with religious and community leaders, and document analysis. The study focuses on identifying and interpreting Islamic values embedded in ritual practices. Findings reveal that key stages of Sasak death rituals—such as bebarak (death announcement), tepong tanak (grave preparation), karang watang (coffin-making), bokos (shroud-cutting), penurut (animal slaughter), and pelangar (ritual food donations)—incorporate Islamic educational values. These include ukhuwah (brotherhood), adab (proper conduct), niyyah (intention), tawakkal (trust in God), and sadaqah (charity). Despite tensions between custom and Islamic jurisprudence, the community maintains a syncretic practice that fosters moral learning. These rituals provide an effective non-formal learning model that contextualizes Islamic teachings through lived experience. The integration of local wisdom with Islamic principles offers a culturally relevant approach to religious education, especially in maintaining community identity and moral development